Growth of pre-sprouted sugarcane seedlings submitted to supplementary lighting - Almeida Neto,Luiz A. (2020)
ABSTRACT Brazil is the largest producer and exporter of sugarcane in the world, and the sugar and ethanol sector has invested in the development of new technologies and methods of planting to meet the market demand. Thus, the aim of this study was to evaluate the performance of sugarcane at the acclimation phase and under field conditions, from pre-sprouted seedlings exposed to supplementary lighting, through light-emitting diode, in the period of acclimation in a greenhouse. The experiment was carried out in Carpina, PE, Brazil, from January to September 2017. The experimental plots were composed of pre-sprouted seedlings acclimated in greenhouse, exposed to the supplementary lighting systems, 90% Red + 10% Blue (R:B 90/10), 80% Red + 20% Blue (R:B 80/20), 70% Red + 30% Blue (R:B 70/30) and a control. The evaluation of seedling growth was performed through the measurement of biometric indicators: plant height (cm); stem length (cm); stem diameter (cm) and number of tillers. The biometric indicators showed no significant differences, but plants under lighting systems with a greater proportion of the red wavelength (R:B 80/20 and R:B 90/10) showed higher percentage of survival in the field.